Consumer Satisfaction with Newborn Pulse Oximetry Screening in a Midwifery-Led Maternity Setting - Elza Cloete; Thomas L. Gentles; Robert A. Lutter; Kelly Richards; Kim Ward; Frank H. Bloomfield (MDPI AG, 2018)
Pulse oximetry screening to detect hypoxaemia in newborn infants was introduced at birthing facilities in New Zealand during a feasibility study determining barriers and enablers to universal screening in a midwifery-led maternity system focused on community values and partnership with, and participation by, consumers. During the 2-year study period, parents of infants who underwent pulse oximetry screening were invited to complete a written survey to investigate consumer satisfaction. Respondents ranked their satisfaction with the test and with information resources on a five-level Likert scale. Additional comments were added in a free text space. Participation was voluntary and anonymous. A total of 657 surveys were included for analysis. Consumers were satisfied with the screening procedure; 94% either agreed or strongly agreed that it is an important health check. Although the quality of information sources was deemed good, a third of participants indicated a wish to obtain more information. Some participants stated that retention of information was an issue, reporting that they were fatigued following the birth. Consumers are receptive to pulse oximetry screening. Sharing information (while considering the receptivity of parents) and engaging the parents of newborn infants are factors that are paramount to the success of newborn screening initiatives.